Immunocompromised children and young people are at no increased risk of severe COVID-19. Issue 1 (January 2022) - Chappell, H.; Patel, R.; Driessens, C.; Tarr, A.W.; Irving, W.L.; Tighe, P.J.; Jackson, H.J.; Harvey-Cowlishaw, T.; Mills, L.; Shaunak, M.; Gbesemete, D.; Leahy, A.; et al.
Highlights: UK immunocompromised paediatric patients were at no increased risk of severe COVID-19. Only 4/38 PCR detected infections were admitted to hospital. None had acute severe COVID-19 or died. Increasing age and immunodeficiency increased reporting of SARS-CoV-2 infection. Worsening of fever, cough and sore throat were associated with reporting SARS-CoV-2 infection. Serology results suggest there was a proportion of SARS-CoV-2 infections undetected by PCR. Abstract: Objectives: We aimed to prospectively describe the incidence and clinical spectrum of SARS-CoV-2 infection in immunocompromised paediatric patients in the UK. Methods: From March 2020 to 2021 weekly questionnaires were sent to immunocompromised paediatric patients or their parents. Information, including symptom presentation and SARS-CoV-2 PCR test results, was collected from 1527 participants from 46 hospitals. Cross-sectional serology was investigated in February and March 2021. Results: Until the end of September 2020, no cases were reported. From September 28th 2020 to March 2021 a total of 38 PCR-detected SARS-CoV-2 infections were reported. Of these, four children were admitted to hospital but none had acute severe COVID-19. Increasing age in association with immunodeficiency increased reporting of SARS-CoV-2 infection. Worsening of fever, cough, and sore throat were associated with participants reporting SARS-CoV-2 infection. Serology data included 452 unvaccinated participants. In those reporting prior positive SARS-CoV-2 PCR, there were detectable antibodies in 9 of 18 (50%). In those with no prior report of infection, antibodies were detected in 32 of 434 (74%). Conclusions: This study shows SARS-CoV-2 infections have occurred in immunocompromised children and young people with no increased risk of severe disease. No children died.